The Transmissional Methodology of Ibn Ḥazm al-Andalusī - Mekki Klaina (Penerbit Hellow Pustaka, 2026)
This study examines the transmissional methodology of Abū Muḥammad Ibn Ḥazm al-Andalusī (d. 456/1064) as a unified critical framework governing his engagement with ḥadīth, historical narration, and the scriptures of the People of the Book. Although modern scholarship has examined his legal and theological views, it has largely overlooked the epistemic unity underlying his treatment of transmitted reports. The central problem addressed here is how Ibn Ḥazm’s ḥadīth-based epistemology -grounded in isnād continuity, narrator uprightness (ʿadālah), and precision (ḍabṭ)- shapes both his ḥadīth criticism and his wider approach to historical and scriptural material, particularly the Torah. Methodologically, the study undertakes close textual analysis of Ibn Ḥazm’s major works in ḥadīth, history, and comparative religion, situating them within the Andalusian intellectual milieu and the methodological heritage of the early muḥaddithūn, and then tracing points of convergence with later Jewish and Western biblical criticism. The findings show that Ibn Ḥazm consistently refuses to accept any report without rigorous external verification and careful examination of its wording and implications, extending classical ḥadīth criteria from prophetic reports to historical narratives and to the Old Testament. He thus emerges as an early architect of a dual critique that combines isnād-based external criticism with close textual scrutiny, anticipating elements later systematized by figures such as Ibn Khaldūn, Ibn Ezra, and Spinoza. The study concludes that Ibn Ḥazm’s method constitutes a coherent and original contribution to the history of ḥadīth criticism and historical methodology, and that his role in the genealogy of scriptural criticism deserves renewed scholarly attention.